Discrepancy Evaluation Model Analysis of Personal-Social Guidance Services at The State University of Malang Laboratory Junior High School - Nuha, Moch. Syihabudin; Hidayah, Nur; Hotifah, Yuliati (Universitas Negeri Semarang, 2024)
Evaluation is an assessment activity carried out by evaluators in order to see an overview of professional work, effectiveness and efficiency of performance. In relation to the field of Guidance and Counseling is the activity of assessing the professional performance of Guidance and Counseling teachers. In this study, a gap model evaluation analysis was conducted. The gap model is a model used to compare the difference between expected conditions and conditions in the field or existing reality. The gap model is the main objective of this research with more specificity on personal-social guidance services. The research method used is a mixed method with a sequential research design. The instrument used is a personal-social guidance service evaluation instrument consisting of 123 statement items. The results showed that the evaluation of Guidance and Counseling teachers in general had gone well; the results of teacher performance in the implementation of personal-social guidance services obtained an average score of 693.6 or 80.5% which fell into the good category; personal-social guidance services at SMP Lab UM have been efficiently implemented by determining topics incidentally; the principal strongly supports the professional development of Guidance and Counseling teachers along with the support system provided through infrastructure in the room and the Guidance and Counseling program. Keywords: evaluation, gap model, personal-social guidance, teacher performance